Geochemical fingerprinting of hydraulic fracturing fluids from Qusaiba Hot Shale and formation water from Paleozoic petroleum systems, Saudi Arabia. Issue 3 (29th April 2016) - Birkle, P.
Abstract: Provenance studies of produced water are essential to trace flow dynamics and reservoir compartmentalization in petroleum systems and to quantify fluid recovery rates from unconventional fracturing. Produced water from a hydraulically fractured well in the Qusaiba Hot Shale in the Northern Exploration Area, Saudi Arabia, was daily monitored and analyzed for water chemistry, and environmental (δ 2 H, δ 13 C, δ 18 OH 2O, δ 18 OSO 4, δ 34 SSO 4, δ 37 Cl, 87 Sr/ 86 Sr) and cosmogenic isotopes ( 3 H, 14 C, 36 Cl), to differentiate from reference fluids of supply water, fracturing fluids, and formation water from adjacent Paleozoic units. Initially, recovered water is composed of fracturing fluids and subsequently replaced by a homogeneous cut of pristine formation water. Formation water is composed of dominant meteoric water (approximately 84 vol%) and minor fossil evaporated seawater. The young 14 C‐apparent age between 6000 and 6700 years BP and depleted δ 18 O/δ 2 H values for the meteoric component confirm the infiltration of surface water into the Qusaiba Hot Shale interval or adjacent units during the Early Holocene Pluvial Period under cooler and wetter climatic conditions than present, which suggest the presence of a very recent, dynamic hydraulic flow system. 36 Cl/Cl ratios between 102 × 10 −15 and 31 × 10 −15 are ambiguous and can be attributed to atmospheric recharge close to the coast, mixing of 36 Cl‐enriched Quaternary meteoric recharge with 36 Cl‐depleted fossil seawater, and/or hypogene production by U‐Th‐enriched host rock. Produced waters from Qusaiba Hot Shale are within the compositional range of Na‐Cl‐type formation water from Paleozoic reservoir units in northern Saudi Arabia with salinities from 30 000 to 130 000 mg l −1 . As a novel technological approach for exploration wells in Northern Saudi Arabia, multi‐isotopic methods were successfully implemented to quantify flowback volumes from hydraulic fracturing, and to fingerprint pristine formation water or pore water in Paleozoic systems on their provenance, residence time, migration pathways, and secondary alteration processes.